2017
DOI: 10.18203/2319-2003.ijbcp20172747
|View full text |Cite
|
Sign up to set email alerts
|

A study of the neuroprotective role of Punica granatum and rosuvastatin in scopolamine induced cognitive deficit in rats

Abstract: Background: The present work has been planned to find out the effect of Punica granatum and Rosuvastatin on learning and memory in Scopolamine induced cognitive deficits in rats. Scopolamine being an anticholinergic agent is used fervently in experimental models for memory deficits and has been widely implicated for the screening of cognitive dysfunction. Punica granatum (Pomegranate) has shown to suppress tumor neuronal cells, hence it can be a potential agent in providing neuroprotection for preventing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As in other research, amnesia is induced using the scopolamine model (2.5 mg/kg) [31]. It has a central action and is a muscarinic cholinergic antagonist.…”
Section: Discussionmentioning
confidence: 96%
“…As in other research, amnesia is induced using the scopolamine model (2.5 mg/kg) [31]. It has a central action and is a muscarinic cholinergic antagonist.…”
Section: Discussionmentioning
confidence: 96%
“…Another study conducted by H. Ahmed et al, (2014) demonstrated that pomegranate seeds at dosages of 100 and 200 mg/kg exhibited cognitive-enhancing effects, potentially through the reduction of Amyloid-β Precursor (Aβ) aggregates in the hippocampus. Additionally, Fatima et al (2017), demonstrated that oral consumption of Punica granatum seeds at a dosage of 500 mg/kg showed ameliorating effects on scopolamine-induced cognitive dysfunction, particularly in the passive avoidance response.…”
Section: Discussionmentioning
confidence: 99%
“…Another study exhibited that pomegranate extract (100 and 200 mg/kg) exerted cognitive‐enhancing effects possibly via the depletion of Aβ aggregates in the hippocampus (Ahmed et al, 2014 ). Furthermore, P. granatum juice (500 mg/kg oral) was shown to ameliorate passive avoidance response in scopolamine‐mediated cognition dysfunction (Fatima et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%